Annual review of information technology developments for economic and social historians, 1993. - Middleton, Roger; Wardley, Peter (Economic History Review, 1994)
The 1993 annual review of information technology developments for economic and social historians. The article includes a summary of recent developments in historical computing and the associated literature; a review of recent hardware and software trends; an update of the 1992 review of spreadsheets, DBMS, and computer assisted learning packages; an account of the development of statistical packages, the criteria for software evaluation, and a comparative review of two leading applications; and an account of the general development of econometrics packages.